Cardiovascular adaptations to 4 and 12 months of football or strength training in 65‐ to 75‐year‐old untrained men. (5th June 2014) - Schmidt, J. F.; Hansen, P. R.; Andersen, T. R.; Andersen, L. J.; Hornstrup, T.; Krustrup, P.; Bangsbo, J.
Abstract : The study examined the effects of 1 year of football or strength training on cardiovascular function in 65‐ to 75‐year‐old men. Twenty‐six untrained men (age: 68.2 ± 3.2 years) were randomized to football training (FTG; n  = 9), strength training (STG; n  = 9), or control (CG; n  = 8). In FTG, left ventricular (LV) internal diastolic diameter, end‐diastolic volume, and mass index were 8%, 21%, and 18% higher ( P  < 0.01), respectively, after 12 months, with no changes in STG and CG. After 12 months, LV ejection fraction was increased ( P  < 0.05) by 8% and 5% in FTG and STG, respectively, and systolic longitudinal two‐dimensional strain by 8% and 6%, whereas right ventricular systolic function improved ( P  < 0.05) by 22% in FTG, but not in STG and CG. In FTG, LV diastolic mitral inflow (E/A) ratio and peak early diastolic velocity (E') improved ( P  < 0.05) by 25% and 12%, respectively, after 12 months, with no changes in STG and CG. In FTG, maximum oxygen uptake was 16% and 18% higher ( P  < 0.001) after 4 and 12 months, respectively, and resting heart rate was 6 and 8 beats per minute lower ( P  < 0.001), respectively, with no changes in STG and CG. In conclusion, football training elicited superior cardiovascular effects compared with strength training in elderly untrained men.